2019
DOI: 10.1192/bjb.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Personal resilience in psychiatrists: systematic review

Abstract: Aims and methodThe concept of personal resilience is relevant to physician well-being, recruitment and retention, and to delivering compassionate patient care. This systematic review aims to explore factors affecting personal resilience among psychiatrists, in particular, those that may impair well-being and those that facilitate resilience practice. A literature search was performed of the Ovid®, Embase®, CINAHL and PsycINFO databases, using keywords to identify empirical studies involving psychiatrists that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…It has been recommended that resilience building should be incorporated into training programmes for healthcare professionals 38. Given the unique stressors that psychiatric professionals encounter, it would be of practical use to implement resilience programmes in this group as well, particularly in the workplace setting 39. Findings from this study would suggest that such programmes can be targeted at younger professionals as they have lower levels of resilience.…”
Section: Discussionmentioning
confidence: 90%
“…It has been recommended that resilience building should be incorporated into training programmes for healthcare professionals 38. Given the unique stressors that psychiatric professionals encounter, it would be of practical use to implement resilience programmes in this group as well, particularly in the workplace setting 39. Findings from this study would suggest that such programmes can be targeted at younger professionals as they have lower levels of resilience.…”
Section: Discussionmentioning
confidence: 90%
“…There is some evidence to suggest that BO is further elevated in the specialty of psychiatry and among trainees. A recent systematic review concluded that psychiatrists, particularly woman and those in training, suffered from higher levels of BO and psychological distress than other medical groups 23. Hayes et al found that younger age, higher effort–reward imbalance and overcommitment were associated with higher BO rates among Irish hospital doctors 9.…”
Section: Discussionmentioning
confidence: 99%
“…10 Physician burnout and the resultant decreased productivity may exacerbate the previously predicted shortfall of 45,000 to 90,000 physicians in the United States by 2025. 11 Occupational stress has resulted in concern about burnout rates among emergency room physicians, 12 anesthesiologists, 13 radiologists, 14 general internists, 15 family physicians, 16 oncologists, 17 psychiatrists, 18 general surgeons, 19 trauma surgeons, 20 physiatrists, 21 cardiologists, 4 dermatologists, 22 obstetrician-gynecologists, 23 gastroenterologists, 24 residents, and even medical students. 25 In addition to worsened patient outcomes and satisfaction, physician health may be at risk.…”
Section: Scope and Impact Of Physician Burnoutmentioning
confidence: 99%